Who knows? Youth work and the mise-en-scene: reframing pedagogies of youth participation. (2nd April 2020) - Batsleer, Janet; Thomas, Nigel Patrick; Pohl, Axel
ABSTRACT: Drawing on the PARTISPACE research (www.partispace.eu) and particularly on findings from three of eight European cities included in the study, this article brings to the surface the dramatic and theatrical practices underlying the metaphor of performance in order to contribute to a better understanding of youth work and youth participation. It considers the spaces, temporalities, actors and audiences, and atmospheres of youth participation projects. Youth workers and young people in these space/times can be seen as actors in the drama of participation; cast in their roles and caught up in power play, both small scale and sometimes on a larger political stage. The micropolitics of group inclusions and exclusions which are pushed beyond the boundary in Youth Council spaces take centre stage in the drama of the Youth Club. Attention to ambivalence in the work of youth workers leads to a discussion of the needs of such pedagogues.